Solar driven photocatalysis as a way to eliminate antibiotics from aquacultures - Silva, Valentina Guimarães da (2022)
To satisfy the world consumption of fish and seafood, the exploitation of aquaculture has been increasing in the last decades. As in other zootechnics, aquaculture uses antibiotics, such as oxolinic acid (OXA) and sulfadiazine (SDZ), for prevention and treatment of diseases. Unfortunately, part of these antibiotics remains in the aquaculture recirculating water systems, as well as in effluents. Thus, the development of sustainable green treatments for antibiotic removal is essential to avoid antibiotics discharge in the aquatic environment and the consequent increase of antimicrobial resistance (AMR). Among these treatments, photodegradation under natural irradiation is a promising alternative. Aiming an efficiency enhancement, the use of semiconductor photocatalysts as titanium dioxide (TiO2) and the versatile carbon quantum dots (CQDs) has risen great interest in the scientific community since they are solar driven photocatalysts, inexpensive to produce and easy to use. In this work, two types of CQDs were synthesized: (i) using citric acid and urea (CQDs-CAU); or (ii) using only citric acid (CQDs-CA). Through a hydrothermal calcination method, different composites were produced by incorporating 4%, 5%, 6% or 8% (w/w) of CQDs in commercial TiO2 (P25). For comparison purposes, calcination was also applied to the single TiO2 and CQDs. The structural characterization of the synthesized photocatalysts was confirmed by X-ray diffraction, Fourier-transform infrared spectroscopy and diffraction reflectance spectrometry, while optical properties were investigated using ultraviolet-visible absorbance and fluorescence spectroscopy. Then, all the materials were tested for OXA and SDZ photocatalysis, namely solutions of each antibiotic (10 mg L -1 ) either in 0.001 mol L -1 phosphate buffer (PB) or in 30 g L -1 synthetic sea salts (SSS), both with pH adjusted to 8.6. In PB, TiO2/CQDs CA 4% (w/w) (500 mg L-1 ) was the most efficient for OXA photodegradation (93.8% removal in 15 min) and SDZ (79.6% removal in 18 min). In SSS, TiO2/CQDs-CA 4% (w/w) (1000 mg L-1) was the most efficient for the degradation of OXA (75.4% removal in 1 h) while CQDs-CAUC (500 mg L-1) was the most efficient for SDZ (69.4% removal in 18 min). The study of photodegradation kinetics using the most efficient photocatalysts and concentrations showed the accentuated decrease of OXA and SDZ half-life time (t1/2). The application of optimal photocatalysis conditions for each antibiotic was tested in brackish aquaculture effluent, where the t1/2 of OXA and SDZ decreased from 3.71 h and 3.98 h to 41.7 min and 4.64 min, respectively. Under these conditions, it was also proved that the bacterial activity of E. coli and V. parahaemolyticus increased with the total photodegradation of OXA and SDZ. Therefore, it was concluded that the produced photocatalysts are efficient in the solar driven removal of OXA and SDZ and in the fight against AMR so they may be used for such a purpose in the sustainable treatment of aquaculture waters.